Early Intervention in Families with Preterm Infants: A Review of Findings from a Randomized Controlled Trial Following Children Up to 9 Years of Age - Stein Erik Ulvund (MDPI AG, 2022)
The Tromsø Intervention Study on Preterms (TISP) randomized 146 preterm born children (<2000 g) either to the Mother-Infant Transaction Program-Modified (MITP-M, n = 72) or to a preterm control group (n = 74). In addition, 75 full-term babies were followed up until 9 years of age. TISP was conducted at the University Hospital Northern Norway (UNN) and only infants who did not have congenital anomalies and families where the mothers' native language was Norwegian were included. The study investigates the effect of MITP-M on cognitive and social development including behavioral problems, quality of life and stress in the family. The results have so far been published in various journals. The aim of this article is to give a comprehensive overall presentation of the main findings and discuss implications for clinical practice and further research. Parents in the intervention group were superior in "reading" their infants' temperament, and at 3, 5 and 7 years of age the intervention group scored significantly higher on well-known tests of cognitive outcome. At 9 years of age, the intervention group had fewer attentional problems, better school achievements and a better quality of life. From the first year onwards, mothers and fathers in the intervention group reported lower levels of stress than parents of in the preterm control group.